Analysis of the Effects of Job Burnout and Psychological Contract Breach on Turnover Intention with Perceived Organisational Support as a Moderating Variable (PT VADS Indonesia, Yogyakarta Branch) - Lindiyani, Citra; Wahyuni, Purbudi; Siswanti, Yuni (International Journal of Economics, Business and Innovation Research, 2026)
This study investigates the effects of job burnout and psychological contract breach (PCB) on turnover intention among contract employees (PKWT) at PT VADS Indonesia, Yogyakarta Branch, with perceived organisational support (POS) as a moderating variable. A quantitative explanatory approach was employed using survey data collected from 140 contract employees selected through simple random sampling. The data were analysed using SEM-PLS with SmartPLS 3.1. The findings indicate that job burnout has a positive and significant effect on turnover intention, suggesting that higher levels of work-related exhaustion increase employees’ intention to leave. Psychological contract breach also shows a positive and significant influence on turnover intention, reflecting the consequences of unmet implicit employment expectations. Furthermore, perceived organisational support moderates both relationships by weakening the positive effects of job burnout and psychological contract breach on turnover intention. These results highlight the strategic role of organisational support in mitigating adverse psychological conditions and enhancing employee retention within the Business Process Outsourcing (BPO) industry